Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
We must solve for x the following equation:
[tex]x^2+6x+9=25.[/tex]1) We pass the +25 on the right to left as -25:
[tex]\begin{gathered} x^2+6x+9-25=0, \\ x^2+6x-16=0. \end{gathered}[/tex]2) Now, we can rewrite the equation in the following form:
[tex]x\cdot x+8\cdot x-2\cdot x-2\cdot8=0.[/tex]3) Factoring the last expression, we have:
[tex]x\cdot(x+8)-2\cdot(x+8)=0.[/tex]Factoring the (x+8) in each term:
[tex](x-2)\cdot(x+8)=0.[/tex]4) By replacing x = 2 or x = -8 in the last expression, we see that the equation is satisfied. So the solutions of the equation are:
[tex]\begin{gathered} x=2, \\ x=-8. \end{gathered}[/tex]Answer
The solutions are:
• x = 2
,• x = -8
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.